The concept of war of the Russian Federation. Military instruments in the Russian power policy in 2014 - Kaszuba, Malina (Przegląd Wschodnioeuropejski, 2023)
The “Russian world” concept is constantly employed in political and media discourse. Despite its active use, no single comprehensive definition exists in scientific literature. In this study, a brief version of the “Russian world” term conceptualization was presented, including two categorical series of semantic formations (social groups and value systems) and three axiological conceptual functions of the “Russian world”. In addition, newly formed narratives in connection with the Russian-Ukrainian war encountered only within the framework of Ukrainian discourse were identified. As research material, Russian and Ukrainian-language texts from the Ukrainian media reflecting the consequences of Russia’s military actions on the territory of Ukraine through the prism of the “Russian world” concept were adopted. The work was conducted applying semantic analysis, contextual analysis, and the substitution method.